HUBUNGAN ANTARA KONSEP DIRI DENGAN SELF- REGULATED LEARNING PADA MAHASISWA PENGHUNI ASRAMA UNIVERSITAS SARI MUTIARA INDONESIA - Sri Ramadhani; Laksana Tobing; Indo Mora; Yurlinawati Baene (JURNAL PSYCHOMUTIARA, 2019)
The process of learning the present College students ' demands for more independent and disciplined in their learning process and set a time. Living in the dorms provide impact for students in terms of their learning process. There are students who are so viewed roommate studying, the student finally join the study. There are also seeing roommates play, the students eventually also come into play. This research aims to know the relationship of the concept of the self with the self-regulated learning on the student boarder University Sari Mutiara Indonesia. The sampling techniques used, namely cluster random sampling. The population of this research is a student boarder University Sari Mutiara Indonesia as many as 180 respondents. The number of samples that is as much as 64 respondents. Test analysis using pearson product moment correlation. The results showed that the concept of the self is the student boarder positive majority of 80%, self-regulated learning student boarder majority simply amounted to 66%, there was a significant relationship between the concept of the self with the self-regulated learning on the student boarder. Where the results of a correlation between the concept of the self with the self-regulated learning of rxy = 0619. Advice to a student boarder is advised to be able to recognize the ability of self, able to set up a schedule of learning and able to fit in with their learning environment.